A crônica vai a guerra: Rubem Braga e os escritos do front - Melo, Mariani Carolina de Souza (2016)
This work has by subject matter the book Crônicas da guerra na Itália, from writer and journalist Rubem Braga. The fabric of the literary work was in 1945, during the Second World War, when Braga traveled to Italy as war correspondent of Diário Carioca, paper in which he was working to follow the FEB Força Expedicionária Brasileira soldiers. In this work are explored the main features of chronicle gender, aspects of its historicity and the connections with the periodic or with the book. It stands out from the chronicles, features as literary lightness, a lack of pretension and humor, however chronicle get other shades, once that, in this case, the condition is the war itself. Given the time and place in which they are written, the narratives merge the historic, the journalistic and literary in its composition. In the same context are mixed the reality lived by the war correspondent and the poetry, constant feature of this lyrical prose writer. To account for the specificity of these writings, was selected a theoretical framework capable of handling memory, the story of the horrors of war and this only place in the narrator witness. The Testimonial Literature, first theoretical choice, studies how the trauma of neighboring events of survivors is presented through language, in the case of chronic, between documentar and fiction. Moreover, to better understanding of the narratives, it was essential some concepts of the German thinker, Walter Benjamin, such as Experience, Storyteller, Threshold and his conception about history. In chronicles analysis, we seek to understand how war changed the lightness of some narratives, how the policial issue is embedded in almost all events, since the departure of Brazilian soldiers to Europe, to the misery of the italian population and how the ferocity of the conflict reached especially the most vulnerable parts: women, children and old men. With keen eye and lyrical writing, the chronicler exceeded the role of a mere correspondent to become a Narrator, in other words, one that transmits experience, turning what he lived in shared sense.